2018
DOI: 10.1101/336859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional diversity of brain networks supports consciousness and verbal intelligence

Abstract: 24How are the myriad stimuli arriving at our senses transformed into conscious thought? 25To address this question, in a series of studies, we asked whether a common mechanism 26 underlies loss of information processing in unconscious states across different conditions, 27 which could shed light on the brain mechanisms of conscious cognition. With a novel 28 approach, we brought together for the first time, data from the same paradigm-a highly 29 engaging auditory-only narrative-in three independent domains: a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 82 publications
0
35
0
Order By: Relevance
“…Although frontal-parietal connectivity did not reliably appear to decrease during general anesthesia, Naci et al recently demonstrated a number of complementary possibilities, including a disrupted frontal-parietal network or a maintained frontal-parietal connectivity that is functionally disconnected from sensory cortex. 48 Lastly, despite the outlined artifact-reduction and filtering strategies, artifactual contamination remains possible. Nonetheless, we have demonstrated the ability to acquire these neurophysiologic data in a pragmatic surgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although frontal-parietal connectivity did not reliably appear to decrease during general anesthesia, Naci et al recently demonstrated a number of complementary possibilities, including a disrupted frontal-parietal network or a maintained frontal-parietal connectivity that is functionally disconnected from sensory cortex. 48 Lastly, despite the outlined artifact-reduction and filtering strategies, artifactual contamination remains possible. Nonetheless, we have demonstrated the ability to acquire these neurophysiologic data in a pragmatic surgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The propofol data employed in this study have been published before (Luppi et al, 2019; Naci et al, 2018; Varley et al, 2020a). For clarity and consistency of reporting, where applicable we use the same wording as our previous study (Luppi et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The characterization of the temporal latency structure in resting may represent a complementary tool for studying brain communication patterns by using fMRI BOLD signals (Mitra and Raichle, 2018). This approach would be highly relevant for the study of altered state of consciousness, for which the transmission, processing of information, as well as the complexity of communication seem disrupted, as suggested by evidence from transcranial magnetic stimulation (Casarotto et al, 2016) and audio stimulus fMRI studies (Naci et al, 2018). By using the time-delay approach, different source or sink brain regions related to high-order functions, such as perception, working memory, and processing of the stimulus, required for the emergence of consciousness, could be further investigated by analyzing their time-delay behaviors (Basar and Düzgün, 2016;Persuh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%